PEMANFAATAN KOMPOS SAMPAH KOTA PADA PERTUMBUHAN DAN HASIL TANAMAN SAWI SENDOK DI TANAH REGOSOL - Pauliz Budi Hastuti; Enny Rahayu; Muhammad Ari Pratama (AGROISTA : Jurnal Agroteknologi, 2017)
This study aims to determine the effect of municipal waste compost on the growth and yield of mustard in Regosols. This research uses factorial experimental methods arranged in complete randomized design. The first factor is the origin of compost from TPS (waste disposal site) consisting of 4 levels namely: TPS Kalasan, TPS Gunung Kidul, TPS Kulon Progo and TPS Bantul. The second factor is compost dose consisting of 4 levels: control + NPK, 120 gram / plant), 180 gram / plant and 240 gram / plant. The results of the observation were analyzed by using analysis of variance (Analysis Of Variance). To know the different treatments were significantly analyzed using Duncan Multiple Range Test (DMRT) at 5% level. The results showed that the composting of municipal waste from various TPS gave the same sprouts growth and yield. While the compost dose of 120 grams / plant has been able to suffice for the growth and yield of mustard plant spoon.